Oncological outcomes of open versus minimally invasive nephroureterectomy for locally advanced upper tract urothelial carcinoma - Afferi, Luca; Pradere, Benjamin; Gallioli, Andrea; Moschini, Marco; Cannoletta, Donato; Soria, Francesco; Juvet, Tristan; Potretzke, Aaron; Djaladat, Hooman; Kikuchi, Eiji; Mari, Andrea; Khene, Zineddine; et al. (World journal of urology, 2025)
INTRODUCTION & OBJECTIVES: It is currently recommended to perform open radical nephroureterectomy (oRNU) with bladder cuff excision in patients with locally advanced (cT3-4 or cN1-2) upper tract urothelial carcinoma (laUTUC). We tested the hypothesis that bladder recurrence-free survival (BRFS), metastasis-free survival (MFS), cancer-specific survival (CSS) and overall survival (OS) are not influenced by the surgical approach in patients with laUTUC using a large multicenter series. MATERIAL & METHODS: This was a multicenter retrospective cohort study including 361 patients with preoperative cT3-4 cM0 or cN1-2 cM0 laUTUC treated with open or minimally invasive RNU from 1999 to 2019 at 21 academic centers in Europe, Asia, and the United States. Missing values of relevant baseline characteristics were estimated through multiple imputation of chained equations. Baseline patients' heterogeneity was balanced using a 1:1 propensity score matching estimated using logistic regression. Uni- and multivariable Cox regression analyses for bladder recurrence, metastasis, cancer-specific death and overall death were performed according to clinical and pathological characteristics. Kaplan Meier (KM) estimates and log-rank test were used to compare BRFS, MFS, CSS and OS according to clinical and pathological features. RESULTS: Median follow-up was 28 months. After propensity score matching, two cohorts of 115 laUTUC patients each with similar baseline and preoperative tumor characteristics were obtained. In the matched cohort, pT ≥ 3 stage was found in 84 (73%) and 67 (58.3%) patients in the oRNU and miRNU groups, respectively. Positive lymph nodes were detected in 27 (23.5%) and 32 (27.8%) patients in the oRNU and miRNU groups, respectively. In the multivariable regression analysis, pT ≥ 3 and positive lymph nodes were associated with an increased risk of metastasis (HR 3.22, 95% CI 1.26-8.23, and HR 4.03, 95% CI 2.05-7.89, respectively). The surgical approach (oRNU vs. mi RNU) did not influence oncological outcomes as shown by uni- and multivariable analyses as well as Kaplan-Meier estimates, regardless of pT stage. CONCLUSIONS: The oncological outcomes of laUTUC for cT3-4 cM0 or cN1-2 cM0 disease are comparable whether RNU is performed via an open or minimally invasive approach. Therefore, the decision to opt for oRNU or miRNU should be guided by the surgeon's expertise and the patient's comorbidities, rather than concerns over long-term oncological outcomes associated with either surgical technique.
Keywords: Male; Treatment Outcome; lidé středního věku; retrospektivní studie; Ureteral Neoplasms; Cohort Studies; staging nádorů; míra přežití; Open nephroureterectomy; Humans; Middle Aged; Survival Rate; senioři; nádory močovodu; Kidney Neoplasms; mužské pohlaví; Female; kohortové studie; Upper tract urothelial cancer; Aged; ženské pohlaví; Nephroureterectomy; Retrospective Studies; miniinvazivní chirurgické výkony; Locally advanced Utuc; Minimally Invasive Surgical Procedures; Utuc; Neoplasm Staging; nefroureterektomie; karcinom z přechodných buněk; lidé; Minimally-invasive nephroureterectomy; Carcinoma, Transitional Cell; nádory ledvin; výsledek terapie